2009
DOI: 10.17014/ijog.v4i4.83
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Lava Dome from the Crater Lake of Kelud Volcano, East Java

Abstract: IntroductIon Geographically the Kelud Volcano is located at 7 o 56'S and 112 o 18'E. The volcano lies within two regencies, i.e. Blitar and Kediri, in East Java (Figure 1). The summit elevation of this stratovolcano is 1731 m asl. and a large lake occupies the summit crater. Historical eruption of the Kelud Volcano was recorded firstly in the year of 1000. The big erup

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 3 publications
1
20
0
Order By: Relevance
“…However, we note that swarms of shallow lowfrequency events can also occur without culminating in eruption, e.g., Shishaldin, 2001-2004(Petersen 2007. Low-frequency and hybrid seismicity can also increase greatly as viscosity increases due to degassing, in which case magma may erupt as a viscous dome, e.g., Pinatubo, 1992 (Ramos et al 1996), and Kelut, 2007(Hidayati et al 2009), or it may stall just before extrusion, e.g., Usu Volcano, 1910and 1943-45 (Minakami et al 1951Yokoyama 2002;Goto et al 2004). (2) Seismic or geodetic evidence of relatively rapid magma ascent (i.e., cm to dm/s).…”
Section: Qualitative Assessments Of Eruption Likelihoodmentioning
confidence: 86%
“…However, we note that swarms of shallow lowfrequency events can also occur without culminating in eruption, e.g., Shishaldin, 2001-2004(Petersen 2007. Low-frequency and hybrid seismicity can also increase greatly as viscosity increases due to degassing, in which case magma may erupt as a viscous dome, e.g., Pinatubo, 1992 (Ramos et al 1996), and Kelut, 2007(Hidayati et al 2009), or it may stall just before extrusion, e.g., Usu Volcano, 1910and 1943-45 (Minakami et al 1951Yokoyama 2002;Goto et al 2004). (2) Seismic or geodetic evidence of relatively rapid magma ascent (i.e., cm to dm/s).…”
Section: Qualitative Assessments Of Eruption Likelihoodmentioning
confidence: 86%
“…After that in August, the sign was followed by an increase of the crater lake water temperature and CO2 concentration. The colour change of crater lake water also recorded from typical green to yellowish in August [1,3,7]. Meanwhile from deformation monitoring showed that continuous uplift occurred at the crater rim from July until early September [7].…”
Section: Sequence Of 2007 Eruption Eventmentioning
confidence: 93%
“…CVHGM raised the level of Kelud activity from level I (normal) to level II (watch) [3]. Two days later on 11 September, VT earthquakes reached 13 events in 5 hours with hypocenters distribution at 2 -4 km below the crater [1]. After that day, VT earthquake event occurred on average one each day.…”
Section: Sequence Of 2007 Eruption Eventmentioning
confidence: 99%
See 1 more Smart Citation
“…Kelud. Hidayati et al [1] responded to the need for detection before the eruption based on color changes to determine the distribution of the crater lake hiposentrum, and Bernard [2] based on water sampling directly of the crater lake, Nandaka and Agung [3] has added a device such as CCTV to observe the smoke activity before eruption. These phenomena known as high activity in the crater lake.…”
Section: Introductionmentioning
confidence: 99%